-(2n-1)-3(n+2)=7

Simple and best practice solution for -(2n-1)-3(n+2)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2n-1)-3(n+2)=7 equation:


Simplifying
-1(2n + -1) + -3(n + 2) = 7

Reorder the terms:
-1(-1 + 2n) + -3(n + 2) = 7
(-1 * -1 + 2n * -1) + -3(n + 2) = 7
(1 + -2n) + -3(n + 2) = 7

Reorder the terms:
1 + -2n + -3(2 + n) = 7
1 + -2n + (2 * -3 + n * -3) = 7
1 + -2n + (-6 + -3n) = 7

Reorder the terms:
1 + -6 + -2n + -3n = 7

Combine like terms: 1 + -6 = -5
-5 + -2n + -3n = 7

Combine like terms: -2n + -3n = -5n
-5 + -5n = 7

Solving
-5 + -5n = 7

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -5n = 7 + 5

Combine like terms: -5 + 5 = 0
0 + -5n = 7 + 5
-5n = 7 + 5

Combine like terms: 7 + 5 = 12
-5n = 12

Divide each side by '-5'.
n = -2.4

Simplifying
n = -2.4

See similar equations:

| -60-9x=124-31x | | x^2-6+24=0 | | 4(2a-8)=(1/7)(49a+70) | | 1=2r | | -7/3x=-6 | | 4(5x-4)+2(19-2x)-5(3x+5)=-13 | | 3w+7y+7x+8x-14y+5w= | | (6y+5)-(3+5y)=7 | | 2x(x-4)=-6 | | 4p+9q=45 | | X+9=6+6x | | 0=5x-20x^3+16x^5 | | x^2-6=7x+12 | | 5x+3=6x+5 | | 8p+8=7p+12 | | -3(3b+2)+(10b-4)=0 | | x/5+3=-6 | | 13x+90= | | x+16.84=8.84 | | 0=x(5-20x^2+16x^4) | | x-16.84=8.84 | | x-8.84=16.84 | | an=5+6 | | 3/7x+5 | | 7(4x+1)=231 | | 0.11x=0.88 | | 1/2(x-9)=2x-4 | | 12(4+d)= | | X^2-2x+6y+6=0 | | 3x-4=x+14 | | x=1/2(2x-4) | | 9d=54 |

Equations solver categories